Exile, a "Second Chance" According to Felicia Mihali? - Eiben, Neli (Oltreoceano - Rivista sulle migrazioni, 2024)
In 2000, disillusioned with Romania's economic situation, Felicia Mihali moved to Montreal, Quebec. There, in the "belle province", by translating into French books she had published in Romania before leaving, she joined a group of migrant writers that included Émile Ollivier, Dany Laferrière, Naïm Kattan, Ying Chen, Abla Farhoud, Marco Micone, Sergio Kokis and others. Initially, she gave her books a second chance through self-translation, and later adopted French and English as her writing languages. Limiting my contribution to the analysis of three of her novels written in French (La reine et le soldat, Dina and La Bigame), the titles of which explicitly refer to women, I propose to examine how the experience of exile is captured in the journey of characters who cross borders and seek to become accustomed to the habits and customs of their host country. Felicia Mihali's writings often conjure up the image of an exile corresponding to what Janet Paterson (2009: 15-16) calls a "transnational subject", i.e. "an emigrant who has either chosen or been forced to leave his or her country of origin. But [...] s/he rejects the notion of an identity formed on the criteria of race or place of origin, in favour of a complex, shifting identity that is often multicultural and outside the confines of memories". Consequently, by modelling the title of my article on the title of her novel, A Second Chance for Adam, I aim to show that in her novels, exile, experienced in a positive way, represents a second chance, given that the protagonists are characterized by a desire for openness and integration into another geographical, linguistic and cultural space.